Journey of Song: Public Life and Morality in Cameroon. Clare A. Ignatowski. 2006. Bloomington: Indiana University press. xv. 223 pp., 36 black and white photographs, maps, bibliography, index. - Shrag, Brian (International Library of African Music, 2007)
pages: 114-116
Keywords: African Music; Cameroon; Morality; Public Life